IMPLEMENTASI KEBIJAKAN LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (E-LAPOR) DALAM PELAYANAN PADA DINAS KOMINFO KABUPATEN JAYAPURA - Gustaf Griapon; Yosephina Ohoiwutun (Universitas Cenderawasih, 2023)
The existence of an e-LAPOR (Layanan Aspirasi dan Pengaduan Online Rakyat) is the implementation of e-Governance to facilitate public service complaints for the community. This study aims to analyze and describe the Implementation of e-LAPOR in Services at Jayapura Regency, Kominfo Service, and to analyze the supporting and inhibiting factors for the Implementation of e-LAPOR in Services at the Regency, Services of Information and Communications Services. Jayapura. This study used a qualitative descriptive approach which was carried out at Jayapura Regency Communication and Informatics Office, the determination of informants was carried out by snowball. Data collection techniques used are observation and interviews. Data analysis includes the stages of data reduction, data presentation, and conclusion. The results of the study show that the implementation of the e-LAPOR Policy in services at the Jayapura District Communication and Information Service has been running but not optimal. In terms of the communication aspect, it has been carried out as it should, by coordinating the policy organizers for information dissemination and socialization in introducing this policy to the target group. In the aspect of human resources, they already have adequate human resources and meet the adequacy aspect, but in terms of the quality of mastery of technical skills it is still lacking, so it is very necessary to hold training to develop the soft skills they have, the institutional environment of facilities is sufficient to carry out the SP4N-LAPOR (Sistem Pengelolaan Pengaduan Pelayanan Publik Nasional Layanan Aspirasi dan Pengaduan Online Rakyat) application is managed by the Admin, access to the internet is also sufficient to run the application. The disposition works quite adequately based on the firmness and seriousness of policy implementers at the institutional level in carrying out the policy. Then, the Bureaucratic Structure is based on the authority and obligation that is handed over by the main tasks and functions of each existing field and section and refers to the SOP (Standard Operational Procedures) for policy implementation. Supporting factors are the existence of regulations at the regional level, the allocation of human resources, and supporting facilities. Then the inhibiting factor is that the community is not very adept at using the e-LAPOR application to make complaints, especially the people at the village level. Then, the lack of outreach to the community and limited access to the internet network in the villages.